History of the pedagogical evaluation of book and didactic material in Brazil (Research, Society and Development, 2020)
This article aims to discuss how the process of qualitative evaluation of the Book and Didactic Material was constituted, during its existence in Brazil, from 1937 to 2017. Therefore, the legal trajectory of the Didactic Book was recovered, as well as the its current execution process since the publication of Decree No. 9,099 / 2017. The presence of the textbook in practically all school institutions of basic Brazilian education has transformed it, over the years, into an important pedagogical tool to support teaching practice, it has even followed the country's schooling process, gaining emphasis from democratization of education (1960). However, only from 1994 we have records of the analysis of the pedagogical, methodological and physical quality of this material. The methodology used in the research is of a qualitative nature, documentary and bibliographic analysis. Initially we did a documentary survey of the Laws and Decrees that supported the preparation, pedagogical evaluation and distribution of books and teaching materials throughout the years 1937 to 2017. Subsequently, the focus was on how this program presents itself today, after publication of Decree No. 9099, of July 18, 2017. We conclude that evaluating the pedagogical quality of the book and didactic material used in the classroom becomes essential, while it assumes a significant role in the school routine, because, among other possibilities , the textbook has a guiding role in teaching practice, without the intention of replacing it.